Go Tani / Ahmad Faiz Azni - Azni, Ahmad Faiz (Universiti Teknologi MARA, Kedah, 2018)
'Go Tani' is a Crop Selling Application that helps farmers market their products by letting farmers and clients sell and buy crops. This application was designed for agriculture industry to help lifting the burden of fellow farmers in selling and buying activities. Difficulty of finding buyers to buy suppliers' (farmers) goods in a large quantity leads to the main objective of this apps. 'Go Tani' makes farmer's job on finding buyers more convenient especially for some of the traditional farmer and also the new farmers. This application will help making difference to agriculture industry in Malaysia. This application is user-friendly and feasible, since the farmers and buyers had chat room for direct communication between them. This will encourage the farmers to sell their crops on their own, and increase their incomes.